A Memetic NSGA-II for the Multi-Objective Flexible Job Shop Scheduling Problem with Real-time Energy Tariffs - Burmeister, Sascha Christian; Guericke, Daniela; Schryen, Guido (Flexible Services and Manufacturing Journal)

Bring me my Meal on your Wheel - An Empirical Analysis of the Impact of Food Delivery Platforms on Local Restaurant Employment - Müller, Michelle; Neumann, Jürgen (Proceedings of the 56th Hawaii International Conference on System Sciences (HICSS))

Is it all about the setting? — A comparison of mathematical modelling with real objects and their representation - Jablonski, Simone (Educational Studies in Mathematics)
Abstract Mathematical modelling emphasizes the connection between mathematics and reality — still, tasks are often exclusively introduced inside the classroom. The paper examines the potential of different task settings for mathematical modelling with real objects: outdoors at the real object itself, with photographs and with a 3D model representation. It is the aim of the study to analyze how far the mathematical modelling steps of students solving the tasks differ in comparison to the settings and representations. In a qualitative study, 19 lower secondary school students worked on tasks of all three settings in a Latin square design. Their working processes in the settings are compared with a special focus on the modelling steps Simplifying and Structuring, as well as Mathematizing. The analysis by means of activity diagrams and a qualitative content analysis shows that both steps are particularly relevant when students work with real objects — independent from the three settings. Still, differences in the actual activities could be observed in the students’ discussion on the appropriateness of a model and in dealing with inaccuracies at the real object. In addition, the process of data collection shows different procedures depending on the setting which presents each of them as an enrichment for the acquisition of modelling skills.

Erzählen zu fantastischen Bildern. Kinder sprechen über Formen und Funktionen grammatischer Mittel in Erzählung - Drepper, Laura (Die Grundschulzeitschrift)

„Es gibt ja Zeichen für Wörter...". Grammatisches und Zeichenhaftes in Sprach(en)repertoires entdecken - Topalović, Elvira; Härtel, Kira (Die Grundschulzeitschrift)

GBP-Monitor: Betriebswirtschaftliche Einschätzungen und Erwartungen von Unternehmen in Deutschland. Unternehmenstrends im November 2023 - Maiterth, Ralf; Sureth-Sloane, Caren; Dyck, Daniel; Heinemann-Heile, Vanessa

The Cost of Tax Simplification: Evidence from Risk-taking in a Turnover-based Corporate Tax System - Amberger, Harald; Siahaan, Fernando; Sureth-Sloane, Caren

Umfrage: Beurteilung Investitionsfördernder Maßnahmen durch Unternehmen im Handwerk - Heinemann-Heile, Vanessa; Maiterth, Ralf; Sureth-Sloane, Caren

2022 Global MNC Tax Complexity Survey - Harst, Simon; Schanz, Deborah; Siegel, Felix; Sureth-Sloane, Caren

Interval incremental learning of interval data streams and application to vehicle tracking - Leite, Daniel; Škrjanc, Igor; Blažič, Sašo; Zdešar, Andrej; Gomide, Fernando (Information Sciences)

Data Driven Fuzzy and Neural Dynamic Systems Modeling - Leite, Daniel; Gomide, Fernando (2023 International Conference on Machine Learning and Cybernetics (ICMLC))

Comparing Humans and Algorithms in Feature Ranking: A Case-Study in the Medical Domain - Hanselle, Jonas Manuel; Kornowicz, Jaroslaw; Heid, Stefan; Thommes, Kirsten; Hüllermeier, Eyke (LWDA’23: Learning, Knowledge, Data, Analysis.)

Telecom C-band photon emission from (In,Ga)As quantum dots generated by filling nanoholes in In0.52Al0.48As layers - Deutsch, Dennis; Buchholz, C.; Zolatanosha, V.; Jöns, K. D.; Reuter, Dirk (AIP Advances)
We present the fabrication of strain-free quantum dots in the In0.53Ga0.47As/In0.52Al0.48As-system lattice matched to InP, as future sources for single and entangled photons for long-haul fiber-based quantum communication in the optical C-band. We achieved these quantum dots by local droplet etching via InAl droplets in an In0.52Al0.48As layer and subsequent filling of the holes with In0.53Ga0.47As. Here, we present detailed investigations of the hole morphologies measured by atomic force microscopy. Statistical analysis of a set of nanoholes reveals a high degree of symmetry for nearly half of them when etched at optimized temperatures. Overgrowth with 50–150 nm In0.52Al0.48As increases their diameter and elongates the holes along the [01̄1]-direction. By systematically scanning the parameter space, we were able to fill the holes with In0.53Ga0.47As, and by capping the filled holes and performing photoluminescence measurements, we observe photoluminescence emission in the O-band up into the C-band depending on the filling height of the nanoholes.

Ein praxisorientiertes Zusammenspiel von Psychomotorik und Tanzimprovisation - Scholz, Maren; Gabriel, Lena (sportpädagogik)

Tanzen, Rhythmus, Darstellen. Die große Spielesammlung - Gabriel, Lena; Teubert, Hilke (Wimasu)

Deciding Subsumption in Defeasible 𝓔𝓛𝓘⊥ with Typicality Models - de Camargo e Souza Câmara, Igor; Turhan, Anni-Yasmin (Logics in Artificial Intelligence)

Ästhetik digitaler Medien. Aktuelle Perspektiven - Flath, Beate (mediendiskurs 17)

Von der "Shallowing Hypothese" zur "Illusion of Understanding" -wie wirken Erklärvideos und Lehrbuchtexte auf Wissen und Verstehensillusion? - Kulgemeyer, Christoph; Sterzing, Fabian Gabriel; Hörnlein, Madeleine

"Aus Erklärvideos lernt man nur oberflächlich" - oder erwirbt man auch Konzeptwissen? - Hörnlein, Madeleine; Kulgemeyer, Christoph

Aus Erklärvideos lernen - Kulgemeyer, Christoph; Sterzing, Fabian Gabriel; Hörnlein, Madeleine (Digital Physik unterrichten. Grundlagen, Impulse, Perspektiven)